2013
DOI: 10.3758/s13414-013-0471-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensory memory of structure-from-motion is shape-specific

Abstract: Perceptual priming can stabilize the phenomenal appearance of multistable visual displays (Leopold, Wilke, Maier, & Logothetis, Nature Neuroscience, 5, 605-609, 2002). Prior exposure to such displays induces a sensory memory of their appearance, which persists over long intervals and intervening stimulation, and which facilitates renewed perception of the same appearance. Here, we investigated perceptual priming for the apparent rotation in depth of ambiguous structure-from-motion (SFM) displays. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 71 publications
4
32
0
Order By: Relevance
“…It is worth to note that recent studies have suggested a distinction between perceptual priming with a brief interval between the prime and target stimuli (e.g., 100ms in the present study) and those with a longer interval (e.g., >1second), the former is usually named neural persistence or inertia (Anstis & Ramachandran, 1987), while the later is usually termed perceptual/sensory memory (Chen & He, 2004; Maier et al, 2003; Pastukhov et al, 2013). For instance, a mask image between the prime and target stimuli will disrupt neural persistence, but not sensory memory (Pastukhov & Braun, 2013).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…It is worth to note that recent studies have suggested a distinction between perceptual priming with a brief interval between the prime and target stimuli (e.g., 100ms in the present study) and those with a longer interval (e.g., >1second), the former is usually named neural persistence or inertia (Anstis & Ramachandran, 1987), while the later is usually termed perceptual/sensory memory (Chen & He, 2004; Maier et al, 2003; Pastukhov et al, 2013). For instance, a mask image between the prime and target stimuli will disrupt neural persistence, but not sensory memory (Pastukhov & Braun, 2013).…”
Section: Introductionmentioning
confidence: 77%
“…More specifically, we test whether the representations of motion direction and object structure of 3-D SFM stimuli are largely independent from each other, or tightly integrated with each other. For instance, with a longer interval between the prime and target stimuli (>1 second), while some previous studies have suggested that motion priming was unaffected by changes of color or shape between prime and target (e.g., Chen & He, 2004; Maier, Wilke, Logothetis, & Leopold, 2003) – suggesting separated neural representations of the motion and object structure of an SFM stimulus, a very recent study has revealed reduced motion priming when the prime and target stimuli constituted different objects (Pastukhov, Füllekrug, & Braun, 2013) – suggesting a rather integrated neural representation for the motion and object structure of a 3-D dynamic object. To further complicate the scenario, a very recent study of motion aftereffect has found that negative motion aftereffect is shape irrelevant (Pastukhov, Lissner, & Braun, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas in the present experiments priming lasted for seconds, other effects induced by recent experience, which may be linked to perception of transformations, retain their influence over far longer time-scales (Klink, Brascamp, Blake, & van Wezel, 2010;Pastukhov & Braun, 2013a;Suzuki & Grabowecky, 2007). Moreover, priming of perceptual states exhibits both facilitatory (Leopold et al, 2002;Orbach, Ehrlich, & Heath, 1963;Pastukhov & Braun, 2013b;Pastukhov, Füllekrug, et al, 2013;Pastukhov, Lissner, Füllekrug, et al, 2014) and inhibitory effects (Pastukhov & Braun, 2011, 2013b operating concurrently on different time-scales. Similarly diverging effects may also exist for priming of transformations.…”
Section: Discussionmentioning
confidence: 59%
“…or is represented and updated locally. To this end, we used the SFM display in conjunction with a selective adaptation procedure (Pastukhov, Füllekrug, & Braun, 2013; to examine how priming strength is affected by a change in the stimulus location, axis of rotation, or shape (see Fig. 7A).…”
Section: Experiments 3 Specificity Of Transformation Primingmentioning
confidence: 99%